Progressive Myoclonus Epilepsy (Lafora Type) - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
The diagnosis of Lafora's syndrome, progressive myoclonus epilepsy and intracytoplasmic periodic acid-Schiff-positive inclusions (Lafora bodies), was made by skin biopsy in a 16-year-old girl at the Depts of Pathology and Dermatology, University of Texas Medical Branch, Galveston, TX.